Szekspir nasz powszedni albo praktyka sensownego czytania w szkole (dziś, tj. „w czasach zarazy cyfrowej” oraz relacji globalnych, a także niezależnie od jakichkolwiek plag czy kataklizmów) - Kłakówna, Zofia Agnieszka (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
The paper is based on the assumption that the contemporary educational system, including its general approach to literature, is characterized by being totally old-fashioned, and its results are completely opposite to what the authors of the relevant programmes hoped to achieve, and this is the reason why it desperately needs re-evaluating and revising. The text documents various motivations of interpreting William Shakespeare’s romantic comedy, The Tempest, as an example of a valuable and meaningful work of fiction. Thus ‘t is a good starting point for a constructive reflection on how to create conditions suitable for studying literature-based texts in the classroom as well as on teachers’ training which would respect both the up-to-date cultural context and the value of humanistic education, paramount for the development of human identity, and which is nowadays widely contested by the present interim economic and technical priorities.
Our Daily Shakespeare or a Sensible Reading Practice in the Classroom (today i.e. at the Time of “Digital Plagues” and Global Relations, as well as Regardless of any Other Plagues or Disasters)
Keywords: humanistic education; practice of contextual fiction reading; reading from the perspective of cultural and philosophical anthropology; literature-based text; theatre production; creating reading conditions; Shakespeare in the classroom; edukacja humanistyczna; praktyka kontekstowego czytania literatury pięknej; czytanie z perspektywy antropologii kulturowej i filozoficznej; tekst literacki; przedstawienie teatralne; projektowanie warunków lektury; Szekspir w szkole